Rejection of learning how to code and the problem of ‘non-use’ in the history of computer cultures - Wasiak, Patryk (medien & zeit. Kommunikation in Vergangenheit und Gegenwart, 2023)
This paper investigates how a host of social actors, such as computer science experts and educators, discursively constructed both positively valued ‘user-programmers’ and negatively valued ‚non-programmers,‘ that is computer users who reject the practice of writing programs on their computers. I argue that the central theme of such a strategy was user agency and the question of having control over the technology that one is using in everyday life. Firstly, I investigate two key themes of the discursive construction of non-programmers in the era of the microcomputer of the 1980s, the discourses towards economies and social development related to computer literacy programs, and next, the key role of programming as a developmental tool for children’s education. Later, I compare that historical era with the contemporary ‘learn to code’ movement and investigate how it outlines the disadvantages of the neglect of learning programming.